Photoelectrocatalytic Properties of Mo-CNT/TiO2 Composite Electrodes under Visible Light - Zhang, Feng-Jun; Oh, Won-Chun (Asian Journal of Chemistry, 2010)
Molybdenum-carbon nanotube (Mo-CNT) and Mo-CNT/titantia (TiO2) composite electrodes were prepared via a sol-gel method and calcincation. The composites were comprehensively characterized by Brauer-Emett-Teller surface area, scanning electron microscopy, energy dispersive X-ray analysis, X-ray diffraction, transmission electron microscopy and UV-vis absorption spectroscopy. The photoelectroactivity of the prepared materials under visible light irradiation was tested using methylene blue in aqueous solution. The result showed that the introduction of molybdenum enhanced the photoelectrocatalytic degradation of methylene blue solution.